Community attitude to the news of pandemic Covid-19 - Rohali Rohali; Siti Perdi Rahayu; Herman Herman; Yeni Artanti; Dwiyanto Djoko Pranowo (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2022)
This study aims to describe the themes and attitudes of the community towards news about the Covid-19 pandemic on WhatsApp. By conducting critical discourse analysis, it is hoped that an understanding will be formed that can enlighten the public on how to interpret and understand the information about the COVID-19 pandemic that they receive through the WhatsApp application and be selective in sending this information to others. The results of the study show the following. Fisrt, the attitude of affection contains 4 themes, namely religious, health, education, and economic themes. There are two functions of a religious theme, namely a request to God and an expression of gratitude. The health theme has three functions, namely an invitation to maintain progress, vaccination recommendations, and health humour. The theme of education is represented in the form of public attitudes regarding the readiness of universities for offline learning. The function of the economic theme is related to expressions of concern and ironism towards the deteriorating Indonesian economy. Second, the attitude of the community's cognition is realized with the theme of health which has the function of protest, fake news, and health humour. Thirth, dehavioral attitudes carry three themes, namely health, education, and economy. The function of the health theme is behaviour in responding to the funeral process for Covid-19 victims and vaccination. The function of the educational theme is related to the behaviour of the community towards the preparation of offline learning. The economic theme is represented by behavioural deviations from health protocols during the implementation of PPKM.Keywords: discourse analysis, attitude, covid-19, WA SIKAP MASYARAKAT TERHADAP BERITA PANDEMI COVID-19 ABSTRAKPenelitian ini bertujuan untuk mendeskipsikan tema dan sikap masyarakat terhadap berita tentang pandemi Covid-19 di WhatsApp. Dengan melakukan analisis wacana kritis, diharapkan akan terbentuk pemahaman yang dapat mencerahkan masyarakat bagaimana memaknai dan memahami informasi tentang pandemi covid-19 yang mereka terima melalui aplikasi WhatsApp dan selektif dalam mengirimkan informasi tersebut ke orang lain. Hasil penelitian menunjukkan hal-hal sebagai berikut. Pertama, sikap afeksi memuat 4 tema yaitu tema religius, kesehatan, pendidikan, dan ekonomi. Ada dua fungsi tema religius yaitu permohonan kepada Tuhan dan ungkapan syukur. Tema kesehatan memiliki tiga fungsi yaitu ajakan menjaga prokes, anjuran vaksinasi, dan humor kesehatan. Tema pendidikan direpresentasikan dalam bentuk sikap masyarakat terkait kesiapan perguruan tinggi dalam pembelajaran luring. Fungsi tema ekonomi berkaitan dengan ungkapan kekhawatiran dan ironisme terhadap ekonomi indonesia yang semakin memburuk. Kedua, sikap kognisi masyarakat diwujudkan dengan tema kesehatan yang memiliki fungsi protes, berita bohong, dan humor kesehatan. Ketiga, sikap perilaku mengusung tiga tema yaitu kesehatan, pendidikan, dan ekonomi. Fungsi tema kesehatan adalah perilaku menyikapi proses pemakaman korban Covid-19, dan vaksinasi. Fungsi tema pendidikan berkaitan dengan perilaku masyarakat terhadap persiapan pembelajaran luring. Tema ekonomi direpresentasikan dengan penyimpangan perilaku terhadap protokol kesehatan di tengah pemberlakuan PPKM.Kata kunci : analisis wacana, sikap, covid-19, WA